Miten tutkia kohteliaisuutta? Käsityksiä suomalaisesta ja ranskalaisesta kohteliaisuudesta - Isosävi, Johanna (Tietolipas, 2023)
Politeness is a key means by which we maintain interpersonal relationships. This book is the first comprehensive study of politeness in Finnish. Based on linguistic and pragmatic research, the book spans three parts. The first part is theoretical and historical, summarising three waves of politeness research, describing politeness as a cultural and historical phenomenon. The second part is empirical, providing an example of the study of im/politeness from outsiders' perspectives-that, is French people living in Finland and Finns living or having lived in France. The focus group discussions ranged from definitions of politeness and differences of behaviour, to learning and teaching as well as to changes to politeness norms within society. The third part summarises the conclusions and offers an epilogue. This reader-friendly book includes exercises and recommended readings, and is welcomed by researchers and students working on politeness and, more broadly, relational work.